Capital Account Liberalization and Inequality - Furceri, Davide (IMF Working Papers; Working Paper ;, 2015)
This paper examines the distributional impact of capital account liberalization. Using panel data for 149 countries from 1970 to 2010, we find that, on average, capital account liberalization reforms increase inequality and reduce the labor share of income in the short and medium term. We also find that the level of financial development and the occurrence of crises play a key role in shaping the response of inequality to capital account liberalization reforms.